Działania 2 Poznańskiego Oddziału Wojsk Ochrony Pogranicza przeciwko grupom zbrojnym na terenie pogranicza = Operations of 2nd Poznań Border Guard Forces (pl. Wojska Ochrony Pogranicza) against armed groups in the border area - Trojanowski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This formation was participating in consolidation of the political system imposed by Moscow. It secured public order and organized armed operations within the area of its jurisdiction i.e. Krosno, Słubice and Gubin County, against armed groups. During these operations, it mainly encountered militias of criminal nature. In the responsibility sector of members of the Krosno Border Guard Forces, there were no activities noted with participation of armed groups belonging to the independence underground. In the period, when the Maneuver Task Force of the Division was involved in the fight against Ukrainian Insurgent Army in Bieszczady Mountains during Wisła Action (pl. Akcja Wisła), this unit has issued improvised emergency subdivisions. The formation in its operations cooperated with field stations of Citizen?s Militia (pl. Milicja Obywatelska) and Security Service (pl. Służba Bezpieczeństwa).
Keywords: 2 Poznański Oddział Wojsk Ochrony Pogranicza; Wojska Ochrony Pogranicza; pogranicze